2017
DOI: 10.1158/1078-0432.ccr-15-2764
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of Both p110α and p110β Isoforms of Phosphatidylinositol 3-Kinase Is Required for Sustained Therapeutic Effect in PTEN-Deficient, ER+ Breast Cancer

Abstract: Purpose Determine the roles of the phosphatidylinositol 3-kinase (PI3K) isoforms p110α and p110β in PTEN-deficient, estrogen receptor α (ER)-positive breast cancer, and the therapeutic potential of isoform-selective inhibitors. Experimental Design Anti-estrogen-sensitive and -resistant PTEN-deficient, ER+ human breast cancer cell lines, and mice bearing anti-estrogen-resistant xenografts were treated with the anti-estrogen fulvestrant, the p110α inhibitor BYL719, the p110β inhibitor GSK2636771, or combinatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
2
13
0
2
Order By: Relevance
“…Similar results were reported by Baselga and colleagues (Schwartz et al, 2015), who found that treatment with a selective p110β inhibitor led to transient suppression of, followed by a significant rebound in phospho-AKT levels, which were attributed to the upregulation of the IGFR1-IRS1-p110α signaling cascade. Similarly, combined treatment with p110α- and p110β-selective inhibitors caused greater tumor growth inhibition in both a PTEN -null prostate cancer and ER + breast cancer models (Hosford et al, 2016). In PTEN -deficient, ER+ breast cancer xenografts, treatment with the triple combination of fulvestrant (a selective estrogen receptor degrader) together with inhibitors of p110α and p110β was required to trigger maximal, sustained tumor regressions.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…Similar results were reported by Baselga and colleagues (Schwartz et al, 2015), who found that treatment with a selective p110β inhibitor led to transient suppression of, followed by a significant rebound in phospho-AKT levels, which were attributed to the upregulation of the IGFR1-IRS1-p110α signaling cascade. Similarly, combined treatment with p110α- and p110β-selective inhibitors caused greater tumor growth inhibition in both a PTEN -null prostate cancer and ER + breast cancer models (Hosford et al, 2016). In PTEN -deficient, ER+ breast cancer xenografts, treatment with the triple combination of fulvestrant (a selective estrogen receptor degrader) together with inhibitors of p110α and p110β was required to trigger maximal, sustained tumor regressions.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…These results were surprising, as the main mechanism of anti-cancer action of anti-estrogens and CDK4/6 i is thought to involve inhibition of cell-cycle progression (58,59). However, evidence suggests that multiple inhibitors that converge at the level of (blocking) P-Rb can synergize despite targeting seemingly redundant pathways (60)(61)(62)(63). In addition, antiproliferative cytokines, such as TGF-b, can increase the threshold for CDK4/6 activation and synergize with CDK4/6 i to induce more complete cell-cycle arrest (64).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor suppressor enzymes prevent uncontrolled activation of the PI3K/AKT/mTORC1 cascade at different levels: among them, PTEN counteracts PI3K activity by dephosphorylating PIP3 to PIP2, while LKB1 indirectly inhibits mTORC1 via AMP-activated protein kinase (AMPK)-mediated activation of TSC1/2 [22,23].…”
Section: Main Textmentioning
confidence: 99%